Marine Heterobranchia (Gastropoda, Mollusca) in Bunaken National Park, North Sulawesi, Indonesia—A Follow-Up Diversity Study - Jan-Hendrik Eisenbarth; Nani Undap; Adelfia Papu; Dorothee Schillo; Jobel Dialao; Sven Reumschüssel; Fontje Kaligis; Robert Bara; Till F. Schäberle; Gabriele M. König; Nathalie Yonow; Heike Wägele (Diversity, 2018)
Bunaken National Park has been surveyed for a fourth time in 14 years, in an attempt to establish the species composition of heterobranch sea slugs in a baseline study for monitoring programs and protection of this special park. These molluscs are potentially good indicators of the health of an ecosystem, as many are species-specific predators on a huge variety of marine benthic and sessile invertebrates from almost every taxonomic group. Additionally, they are known to contain bio-compounds of significance in the pharmaceutical industry. It is therefore of paramount importance not only to document the species composition from a zoogeographic point of view, but to assist in their protection for the future, both in terms of economics and aesthetics. These four surveys have documented more than 200 species, with an approximate 50% of each collection found only on that survey and not re-collected. Many species new to science have also been documented, highlighting the lack of knowledge in this field.